An ANALYSIS OF SMALL GROUP DISCUSSION IN TEACHING ENGLISH SPEAKING CLASS IN BASIC LEVEL AT BRILLIANT ENGLISH COURSE KAMPUNG INGGRIS PARE - Dewi, Fatqu Rofiqoh; Sholikhan, Lukman H (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2024)
The subject of this research consists of one class. Engaged an English teacher, and 11 students in the Brilliant Pare English Course. The steps of this research are conducting observations, interviews, and documentation. The research data is qualitative. Qualitative data were obtained by observing the teaching and learning process during the implementation of the action. Data was collected in the form of field notes, interviews and documentation. The research findings show that the learning system at Brilliant English Course is almost the same as a formal school and uses small group discussion methods. Indicators of successful implementation are: (1) students are more active in speaking English routines using the small group discussion method (2) students are more enthusiastic in carrying out English speaking routines; And (3) students' self-confidence and motivation to speak English increase. In addition, students are also motivated to learn English and are encouraged to focus on the teaching and learning process by using small group discussions in learning speaking. so as to be able to understand the material easily and provide participation or do the task actively.